KARAKTERISTIK KIMIA LATOSOL PACIRAN DAN PERTUMBUHAN BAYAM AKIBAT APLIKASI PUPUK ORGANIK LIMBAH TANAMAN PISANG - Aprilia, Anisa; Peniwiratri, Lelanti (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2026)
The abundant banana plant waste in Paciran, Lamongan, East Java, poses a risk of environmental pollution, but it also contains plant nutrients such as nitrogen, phosphorus, potassium, and organic matter that have the potential to improve the chemical characteristics of Paciran Latosol. This study aims to determine how liquid and solid organic fertilizers derived from banana plant waste in Paciran affect the chemical characteristics of Latosol and to examine how the application of organic fertilizers influences spinach growth. The study employed a non-factorial completely randomized design with nine treatments and three replicates. The treatments included: No Organic Fertilizer Application (P0), Liquid Organic Fertilizer Application at 0.22 ml/pot (equivalent to 25 L/ha) (P1), 0.44 ml/pot equivalent to 50 L/ha (P2), 0.66 ml/pot equivalent to 75 L/ha (P3), 0.88 ml/pot equivalent to 100 L/ha (P4), Application of Solid Organic Fertilizer at 4.36 g/pot, equivalent to 5 tons/ha (P5), 8.72 g/pot equivalent to 10 tons/ha (P6), 13.08 g/pot equivalent to 15 tons/ha (P7), and 20 tons/ha (P8). The results of the study indicate that the application of organic fertilizer has a significant effect on increasing the pH of H₂O, organic carbon, cation exchange capacity (CEC), available nitrogen, available phosphorus, and available potassium in Latosol, as well as on spinach growth, including plant height, number of leaves, and fresh weight. The application of solid organic fertilizer at a rate of 13.08 g/pot, equivalent to 15 tons/ha (P7), yielded the best results in improving both the chemical characteristics of Latosol and spinach growth.